Statyka Rozgałęzionych Przestrzennych Rurociągów Samokompensacyjnych - Woźniak, C. (Engineering Transactions, 1963)
The state of stress and displacement in a spatial branched pipe line is analysed. Next, a method is proposed for determining the forces and moments due to the influence of temperature and continuous load. This method introduces in the computation procedure of the pipe line iteration methods for equilibrating forces and moments. The method is illustrated by a numerical example.